The Roles of Noncoding RNAs in the Development of Osteosarcoma Stem Cells and Potential Therapeutic Targets - Liu, Jinxin; Shang, Guanning (Frontiers in Cell and Developmental Biology, 2022)
Osteosarcoma (OS) is the common bone tumor in children and adolescents. Because of chemotherapy resistance, the OS patients have a poor prognosis. The one reason of chemotherapeutic resistance is the development of cancer stem cells (CSCs). CSCs represent a small portion of tumor cells with the capacity of self-renewal and multipotency, which are associated with tumor initiation, metastasis, recurrence and drug resistance. Recently, noncoding RNAs (ncRNAs) have been reported to critically regulate CSCs. Therefore, in this review article, we described the role of ncRNAs, especially miRNAs, lncRNAs and circRNAs, in regulating CSCs development and potential mechanisms. Specifically, we discussed the role of multiple miRNAs in targeting CSCs, including miR-26a, miR-29b, miR-34a, miR-133a, miR-143, miR-335, miR-382, miR-499a, miR-1247, and let-7d. Moreover, we highlighted the functions of lncRNAs in regulating CSCs in OS, such as B4GALT1-AS1, DANCR, DLX6-AS1, FER1L4, HIF2PUT, LINK-A, MALAT1, SOX2-OT, and THOR. Due to the critical roles of ncRNAs in regulation of OS CSCs, targeting ncRNAs might be a novel strategy for eliminating CSCs for OS therapy.